1983
DOI: 10.1007/bf02001577
|View full text |Cite
|
Sign up to set email alerts
|

Latex agglutination test for detection of Candida antigen in patients with disseminated disease

Abstract: A latex agglutination test has been devised which allows detection of a circulating antigen in patients with systemic infection due to Candida albicans, Candida tropicalis and Candida parapsilosis. Latex is sensitized with serum from rabbits immunized with whole heat killed Candida albicans blastoconidia. The active component of this serum is IgG. Control latex, used to differentiate non-specific agglutination, is sensitized with the same dilution of serum from a rabbit without antibody to Candida species. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 14 publications
2
74
1
1
Order By: Relevance
“…The mixture was precipitated by centrifugation at 3,000 rpm for 15 min and the supernatant was neutralized with NaOH before use in the limulus tests. Candida antigen was measured by Cand-tec (Ramco Lab., Houston, TX, USA) according to the manufacturer's instructions (Gentry et al 1983). Twenty-microliter quantities of rabbit serum and 20 p 1 of anti-candida antibody coated latex were mixed on glass slides.…”
Section: Experimental Candidiasis In Rabbitsmentioning
confidence: 99%
“…The mixture was precipitated by centrifugation at 3,000 rpm for 15 min and the supernatant was neutralized with NaOH before use in the limulus tests. Candida antigen was measured by Cand-tec (Ramco Lab., Houston, TX, USA) according to the manufacturer's instructions (Gentry et al 1983). Twenty-microliter quantities of rabbit serum and 20 p 1 of anti-candida antibody coated latex were mixed on glass slides.…”
Section: Experimental Candidiasis In Rabbitsmentioning
confidence: 99%
“…a major candidal metabolite, is a useful parameter in the prompt diagnosis of Candida pyelonephritis in candiduria patients [16], However, the measurement kit is only limitedly available in Japan and, in addition, some other methods such as enzyme-linked immunosorbent, gas-liquid chromato graphic or spectrofluorometric assays are complicated, time-consuming and, in part, expensive. On the other hand, since the CAND-TEC assay has the advantages described above, its usefulness in patients with various Candida infections has been investigated [1][2][3][4][5][6][7][8], This assay which detects candidal protein antigen, not mannans [1], is apparently specific for the fungal antigen which circulates in the sera of patients with infections caused by C. albicans, C. tropicalis or C. parapsilosis [2], This test was recently reported to be unreliable [5][6][7] because the antigen detected by this assay has not been identified [ 1,3], while the positive threshold has not been decided [3]. In addition, renal function, as well as the presence of rheumatoid factor [2], leads to a false-positive elevation of the titer [5,6], although this was not found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, a commercial test, the Candida Detection System (CAND-TEC™; Ramco Laboratories, Inc., Houston. Tex., USA), has been developed and since this test is relatively cheap, requires little time and is simple to use several investiga tors have examined its usefulness in patients with vari ous forms of Candida infection [1][2][3][4][5][6][7] including candid uria [8],…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the CAND-TEC assay for diagnosis of invasive candidiasis in patients with a variety of underlying diseases has been explored in four studies (19,36,37,52). The authors reported diagnostic sensitivities between 19 and 91% and specificities between 89 and 95%.…”
Section: Detection Of Candida Antigens In Seramentioning
confidence: 99%
“…In each of these studies, different criteria for diagnosing invasive candidiasis were used, and in many instances the descriptions of patients with invasive candidiasis were too limited to confirm that they had invasive infection rather than colonization or superficial infection by Candida spp. Also, in three studies (19,36,37), the control sera tested were from either healthy volunteers or patients who were not clearly matched with the infected patients for underlying disease. These problems make these studies different to interpret.…”
Section: Detection Of Candida Antigens In Seramentioning
confidence: 99%